Social Business Process Management and Knowledge Intensive Processes (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2016)
Business process management (BPM) is a worldwide spread holistic management discipline which increases organizational performance by managing its business processes. A number of researchers indicate the need for further examination of the role of organizational culture in BPM and its maturity. In addition, there has been a recent development of social BPM as an effort to overcome the traditional BPM limitations by using social software for managing the organizations’ business processes and increasing collaboration between BPM project teams. Therefore, we conducted a case study in one Croatian IT company which operates as a consultant company and deals with software implementation. Since their processes are knowledge intensive, they are not always formal and structured so social BPM helps the company with process change and optimization. The aim of this paper is to examine the role of organizational culture and social software usage on BPM maturity in the observed company.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.